The unsung heroes - Ahmad, Afida; Najib, Liana; Samsudin, Syafiza Saila (Universiti Teknologi MARA, Kedah, 2024)
As our world becomes increasingly intricate, harnessing the synergy between technology and economics to metamorphose societies into industrial juggernauts offers innovative means of reshaping our global landscape. The Industrial Revolution (IR) has undergone several phases: IR 1.0 marked the shift from manual to mechanized manufacturing; IR 2.0 emphasized mass production and electricity; IR 3.0 witnessed the ascendancy of computers and automation; IR 4.0, often referred to as the digital era, introduced the concepts of the Internet of Things (IoT), Artificial Intelligence, and data connectivity as integral components of daily life; and IR 5.0 ushered in a more advanced and holistic approach, emphasizing collaboration between humans and machines while taking into account sustainability and socially responsible industrial practices.